Bacillus megaterium NCT-2 agent alters soil nutrients, vegetable quality, and root microecology in secondary salinized soil - You, Yimin; Li, Shitong; Wang, Liran; Zhao, Xiyang; Zhang, Dan; Chu, Shaohua; Yang, Xijia; Zhou, Pei (Frontiers in Microbiology, 2025)
Microbial remediation technology has the characteristics of high efficiency and environmental protection, which has attracted attention. However, there is complexity in the microorganism-soil–plant system. The effects of microbial agents on soil nutrients, plant quality, rhizosphere, and endophytic microorganisms are still unclear. Here, we demonstrate the application of Bacillus megaterium NCT-2 as a multifunctional agent that concurrently addresses salinization-driven nutrient imbalances and reshapes keystone microbial taxa to restore soil–plant homeostasis. The results showed that NCT-2 agent improved the soil nutrients, reduced the loss of nitrogen and sulfur, increased the content of available phosphorus, and decreased the electrical conductivity. The agent increased the number of bacteria and fungi in the soil. Meanwhile, NCT-2 agent improved the vegetable quality and yield. Specifically, the NCT-2 agent significantly increased the aboveground fresh weight, underground fresh weight, total flavonoids, antioxidant enzyme activity, ascorbic acid, Cu, Zn, Fe, P, and K in lettuce, while significantly reduced nitrate. The chlorophyll a, chlorophyll b, carotenoids, and total chlorophyll were significantly increased by the agent. Critically, high-throughput sequencing revealed NCT-2-driven enrichment of stress-resilient taxa (e.g., Firmicutes, Acidobacteria) and functional synergists (e.g., Acetobacter), which correlated with soil nutrient fluxes and plant antioxidant capacity. By decoupling the interplay between microbial community restructuring and systemic remediation outcomes, this work establishes a novel framework for leveraging keystone taxa to optimize salinized agroecosystems.